Peran Komunitas Gerakan Pesantren Sehat (GPS) Jambi dalam Meningkatkan Pengetahuan Kesehatan Mental Santri di Pondok Pesantren Daaru Attauhiid Kec. Kumpeh ulu kab. Muaro jambi - Dina Afriani (JIGC (Journal of Islamic Guidance and Counseling), 2020)
This research is motivated by the existence of the Healthy Pesantren Movement Community (GPS) in Jambi which has the role of increasing health knowledge for students in the boarding school environment. The purpose of this study was to determine the daily life of students at the Daaru Attauhiid Islamic boarding school, to know efforts to increase students' knowledge about health. This research method is qualitative using data collection techniques through observation for 40 days at the Daaru Attauhiid Islamic boarding school, from January to April 2020. Interviews were also conducted with 13 informants, and researchers conducted documentation of data related to the theme of this study. The data obtained were analyzed through three stages, data reduction, data presentation and data verification. The results of the study found that: First, the daily life of santri in the Daaru Attauhiid Islamic boarding school is like santri in general, both in terms of awareness, knowledge and learning and teaching facilities. Santri pondok are so lacking in developing mental health knowledge. Secondly, GPS Jambi has tried to increase the knowledge of santri Daaru Attauhiid in improving the mental health of santri, such as providing material understanding and education on mental health knowledge by means of socialization and the Jambi GPS program to approach the santri story and Sharing session. Third, the supporting factors of GPS Jambi collaborate with other parties, such as introducing GPS Jambi to residents of Islamic boarding schools, especially to students who need a helping hand. The inhibiting factors are; the students' lack of knowledge about mental health so that many terms and materials related to mental health should be given more at the beginning. The lack of interest of students to add insight and understanding about mental health, because it has not been considered important is another obstacle. The researcher recommends that GPS Jambi members or volunteers, develop the GPS Jambi vision and mission by increasing disciplined activities and monitoring the target, especially in providing mental health knowledge to students.